12 - Book Review: Handbook on Society and Social Policy By Nick Ellison and Tina Haux (Eds.) Edward Elgar Publishing, Cheltenham, UK and Northampton, MA USA. ISBN 978 1 78811 3519 (cased) - Oloyede, Olajide (African Sociological Review, 2022)
Abstract